2013
DOI: 10.1136/bmj.f653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telehealth on quality of life and psychological outcomes over 12 months (Whole Systems Demonstrator telehealth questionnaire study): nested study of patient reported outcomes in a pragmatic, cluster randomised controlled trial

Abstract: Effect of telehealth on quality of life and psychological outcomes over 12 months (Whole Systems Demonstrator telehealth questionnaire study): nested study of patient reported outcomes in a pragmatic, cluster randomised controlled trial AbstractObjective To assess the effect of second generation, home based telehealth on health related quality of life, anxiety, and depressive symptoms over 12 months in patients with long term conditions.Design A study of patient reported outcomes (the Whole Systems Demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(204 citation statements)
references
References 74 publications
(77 reference statements)
8
189
2
5
Order By: Relevance
“…Regarding year of publication, nine articles were dated 2012 (15)(16)18,(20)(21)(22)(29)(30)(31) , followed by years 2011 (n=6) (11)(12)(13)17,19,23,33) , 2010 (n=4) (24)(25)32,34) , 2013 (n=3) (14,(27)(28) and 2008 (n=1) (26) . The articles were published in General Cardiology journals (12)(13)(16)(17)(18)20,22,(24)(25)(28)(29)(30)(31)(32)34) , followed by General Clinical journals (14)(15)(26)(27)33) . Two articles were published in Nursing journals (19,23) and one was published in a Nutrition journal (21) (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding year of publication, nine articles were dated 2012 (15)(16)18,(20)(21)(22)(29)(30)(31) , followed by years 2011 (n=6) (11)(12)(13)17,19,23,33) , 2010 (n=4) (24)(25)32,34) , 2013 (n=3) (14,(27)(28) and 2008 (n=1) (26) . The articles were published in General Cardiology journals (12)(13)(16)(17)(18)20,22,(24)(25)(28)(29)(30)(31)(32)34) , followed by General Clinical journals (14)(15)(26)(27)33) . Two articles were published in Nursing journals (19,23) and one was published in a Nutrition journal (21) (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies were performed in the following countries: USA (n=8) (12,15,17,19,(24)(25)(32)(33) , Sweden (n=2) (18,23) , Germany (n=2) (22,34) , Brazil (n=2) (21,26) , Australia (n=2) (28)(29) , United Kingdom (n=2) (14,31) , Italy (n=2) (16,30) , Spain (n=1) (13) , Taiwan (n=1) (19) and Iran (n=1) (27) . Nurses were the professionals performing the interventions in most studies (12,(14)(15)(19)(20)32) . Another study was performed by nurses in partnership with physical therapists (24) or physicians (22) , followed by nurses working with physical therapists, physicians and occupational therapists (18) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show inconsistent results in patient benefits, expected cost savings, and so forth. For example, some studies have shown measurable improvements in patient outcomes (Miguel et al, 2013); others have been neutral (Cox et al, 2012); while others reported no meaningful impact (Cartwright et al, 2013). The area of telehealth is still relatively immature and will continue to evolve over the next decade.…”
Section: Home-based Clinical Applicationsmentioning
confidence: 99%